Is 1/sec^2(θ) the same as cos^2(θ)

Answers

Answer 1
Answer: (1)/(sec^2\theta)=cos^2\theta\n\nL=(1)/(\left((1)/(cos\theta)\right)^2)=(1)/((1)/(cos^2\theta))=1:(1)/(cos^2\theta)=1\cdot(cos^2\theta)/(1)=cos^2\theta=R

Related Questions

Write the function for the graph.f(x)10-(1,8)(0,4)A. f(x) = 4 . (2)B. f(x) = 8. (4)*C. f(x) = 4. (8)*D. f(x) = 2 · (4)
If ON = 8x – 8, LM = 7x + 4, NM = x – 5, and OL = 3y – 6, find the values of x and y for which LMNO must be a parallelogram. The diagram is not drawn to scale. pic and medal
Every month Neha takes a fixed amount of ₹3750 from her mother for her expenses. What is the amount she is spending in a year. What is the quality reflected here?
Mars takes 686 days to orbit the Sun. What percent is this of the time it takes the Earth to orbit the Sun?
Use Gaussian elimination to solve the following system of linear equations -2x_1+3x_2 + x_3 = 2 -3x_1+4x_2 + 2x_3 = 2 x_1-5x_2+4x_3 = -9 -2x_1+4x_2-4x_3 = 8

Divide.6,859 ÷ 79

The quotient is

and the remainder is
.

Answers

Answer:

86, 65

Step-by-step explanation:

Quotient is 86

Remainder is 65

ABCD is a rectangle. find m  <AEB

Answers

Answer:

\Rightarrow m\angle AEB=130^(\circ)

Step-by-step explanation:

As ABCD is a rectangle. So each angle of the rectangle is 90° and m\angle EAD=65^(\circ), so

m\angle EAB=90^(\circ)-65^(\circ)=25^(\circ)

The diagonals of the rectangle bisects each other. Hence,

\Rightarrow AE=BE

In a triangle if two sides are equal then the angles opposite them will be equal.

So in triangle AEB,

m\angle EBA=m\angle EAB=25^(\circ)

As the sum of the angles in a triangle adds up to 180°, so

\Rightarrow m\angle EBA+m\angle EAB+m\angle AEB=180^(\circ)

\Rightarrow m\angle AEB=180^(\circ)- m\angle EBA-m\angle EAB

\Rightarrow m\angle AEB=180^(\circ)-25^(\circ)-25^(\circ)=130^(\circ)

Remove all grouping symbols and combine like terms.( 3x + x ^2) - { 4x^2 - 3x +[ 2x^2 - x - (5x^2 + 4x)]}
Thank you

Answers

(3x+x^2)-\{4x^2-3x+[2x^2-x-(5x^2+4x)]\}\n\n=3x+x^2-\{4x^2-3x+[2x^2-x-5x^2-4x]\}\n\n=3x+x^2-\{4x^2-3x+[-3x^2-5x]\}\n\n=3x+x^2-\{4x^2-3x-3x^2-5x\}\n\n=3x+x^2-\{x^2-8x\}\n\n=3x+x^2-x^2+8x\n\n=11x
( 3x + x ^2) - (4x^2 - 3x +(2x^2 - x - (5x^2 + 4x)))=\n 3x+x^2-4x^2+3x-(2x^2-x-5x^2-4x)=\n -3x^2+6x-2x^2+x+5x^2+4x=\n 11x

Cómo se puede describir a la regla o patrón de una sucesión .? *a)Expresión de números cortos.
b)Expresión algebraica.
c)Expresión multiple.

Answers

¡Hola! Creo que tu respuesta es una expresión algebraica B, aunque no estoy 100% seguro. ¡Espero que esto te ayude! Buena suerte y que tengas un gran día. ❤️

Felipe has saved $625. He is starting a part-time job that pays him $150 a week, and he plans to save all of the money he earns. Which algebraic expression represents Felipe's total savings after x weeks? A.625x + 125 B.775x C.150x + 625 D.125x - 650

Answers

The answer is C, 150x+625
Where x is the number of weeks

Answer:

The correct answer is C. 150x + 625 because x equals the total number of weeks. Hope this helps!

The sum of a number and 19 is at least 8.2.

Answers

Well the equation for this is = x+19>=8.2
X = a number which is the sum   |    it says and so that's + 19 is at least 8.2 so this means is = to 8.2. Your equation should be set up like this : x+19=8.2.